Imunodiagnóstico de Aeromonas hydrophila em pacus (Piaractus mesopotamicus, Holmberg, 1887) infectados experimentalmente - Fernandes, Dayanne Carla [UNESP] (2015)
Among the aeromonas complex, Aeromonas hydrophila has the potential to infect mammals, fish, and humans. It is a cosmopolitan, opportunistic and emerging pathogen in nosocomial infections in humans. This bacteria complex formed by several subspecies also presents antigenic variety, which makes diagnosis difficult to be done with the use of monoclonal antibodies. The aim of this work was to produce polyclonal immunoglobulin Y purified from yolk of laying hens, immunized with bacterial membrane proteins, and to test its effectiveness in immunohistochemistry of A. hydrophila cells in the liver and kidney of experimentally infected Piaractus mesopotamicus. The results showed that the laying hens produced specific anti-A. hydrophila antibodies in serum and yolk, with a significant (p<0,05) and progressive increase of titles at 60 days, which were maintained until 90 days after the third detectable immunization in the ELISA test. The immunohistochemistry was positive for detection of colonies of A. hydrophila in liver and P. mesopotamicus in heart, liver, kidney, brain and spleen with the use of specific IgY antibodies. Therefore, the immunoglobulin produced in chicken eggs was effective in diagnosing aeromonas in P. mesopotamicus